Renal failure suppresses muscle irisin expression, and irisin blunts cortical bone loss in mice. Issue 1 (7th January 2022) - Kawao, Naoyuki; Kawaguchi, Miku; Ohira, Takashi; Ehara, Hiroki; Mizukami, Yuya; Takafuji, Yoshimasa; Kaji, Hiroshi
Abstract: Background: Chronic renal failure induces bone mineral disorders and sarcopenia. Skeletal muscle affects other tissues, including bone, by releasing myokines. However, the effects of chronic renal failure on the interactions between muscle and bone remain unclear. Methods: We investigated the effects of renal failure on bone, muscle, and myokines linking muscle to bone using a mouse 5/6 nephrectomy (Nx) model. Muscle mass and bone mineral density (BMD) were analysed by quantitative computed tomography 8 weeks after Nx. Results: Nephrectomy significantly reduced muscle mass in the whole body (12.1% reduction, P < 0.05), grip strength (10.1% reduction, P < 0.05), and cortical BMD at the femurs of mice (9.5% reduction, P < 0.01) 8 weeks after surgery, but did not affect trabecular BMD at the femurs. Among the myokines linking muscle to bone, Nx reduced the expression of irisin, a proteolytic product of fibronectin type III domain‐containing 5 (Fndc5), in the gastrocnemius muscles of mice (38% reduction, P < 0.01). Nx increased myostatin mRNA levels in the gastrocnemius muscles of mice (54% increase, P < 0.01). In simple regression analyses, cortical BMD, but not trabecular BMD, at the femurs was positively related to Fndc5 mRNA levels in the gastrocnemius muscles of mice ( r = 0.651, P < 0.05). The weekly administration of recombinant irisin to mice ameliorated the decrease in cortical BMD, but not muscle mass or grip strength, induced by Nx (6.2% reduction in mice with Nx vs. 3.3% reduction in mice with Nx and irisin treatment, P < 0.05). Conclusions: The present results demonstrated that renal failure decreases the expression of irisin in the gastrocnemius muscles of mice. Irisin may contribute to cortical bone loss induced by renal failure in mice as a myokine linking muscle to bone.